1996
DOI: 10.1016/s0741-5214(96)70015-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a femoral arteriovenous fistula on lower extremity venous hemodynamics after femorocaval reconstruction

Abstract: AVFs increased flow through the femorocaval grafts, yet they impeded venous return. The ideal AVF-to-graft ratio used in our study was 0.375, because it increased graft flow, permitted forward flow in the femoral vein while reducing pressure, and improved venous return with exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
(2 reference statements)
2
12
0
Order By: Relevance
“…5,6 Recent studies have shown, however, that surgical thrombectomy may provide long-term iliac venous patency rates of approximately 80% when combined with the creation of an arteriovenous fistula. [7][8][9] However, for many patients, thrombectomy is incomplete, with early occurrence of rethrombosis. As a result, venous thrombectomy has not been accepted as the standard treatment for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent studies have shown, however, that surgical thrombectomy may provide long-term iliac venous patency rates of approximately 80% when combined with the creation of an arteriovenous fistula. [7][8][9] However, for many patients, thrombectomy is incomplete, with early occurrence of rethrombosis. As a result, venous thrombectomy has not been accepted as the standard treatment for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both 5-mm and 6-mm AVFs are assumedly sufficient to reach that point, which is consistent with previous research. 17 Since placing the PTFE in a loop or a straight did not influence results, it is apparently not relevant whether flow enters the vein in an antegrade or retrograde direction. Ostensibly, outflow of the lower limb does not seem to suffer under the initial different flow direction of the blood from the AVF.…”
Section: Discussionmentioning
confidence: 96%
“…Usage of SFA as an autologous graft to reconstruct SFV makes it unnecessary to constitute an AVF as described in the literature to improve patency of venous reconstruction. 6 Utilization of the SFA as an autograft has been reported for popliteal aneurysm repair and carotid artery reconstruction in the absence of conventional venous conduits. 7,8 Ghosh et al 9 reported successful use of an SFA autograft as a femoral vein replacement on a 46-year-old-man during en bloc sarcoma resection.…”
Section: Discussionmentioning
confidence: 99%